Students' Mathematical Communication Skills in Terms of Concrete and Abstract Sequential Thinking Styles - Utami, Lintang Fitra; Pramudya, Ikrar; Slamet, Isnandar (Al-Jabar: Jurnal Pendidikan Matematika, 2020)
This study aimed to analyze and describe the eleventh-grade senior high school students' mathematical communication skills on linear program material in terms of concrete and abstract sequential thinking styles. This study employed a qualitative descriptive approach with the case study method. The sampling technique used was the purposive sampling technique. The mathematical communication skills test and thinking style questionnaires were employed as the data collecting technique. The analysis revealed that subjects in the AS category could make generalizations based on good reasoning in the written text aspect. On the other hand, subjects in the CS category were having a hard time constructing abstract assumptions. In the drawing aspect, subjects in the AS category showed good theories and concept understanding. In contrast, subjects in the CS category were only able to apply some of the information to draw graphs. In mathematical expressions, subjects in the AS category could process the information implied by the problem to make mathematical models correctly. Meanwhile, subjects in the CS category needed additional information or direction to understand the information to avoid mistakes.